2014
DOI: 10.5194/amt-7-887-2014
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cloud liquid water path from SEVIRI onboard the Meteosat Second Generation 2 satellite for several cloud types

Abstract: Abstract. In this study the temporal and spatial characteristics of the liquid water path (LWP) of low, middle and high level clouds are analysed using space-based observations from the Spinning Enhanced Visible and Infrared Imager (SEVIRI) instrument onboard the Meteosat Second Generation 2 (MSG 2) satellite. Both geophysical quantities are part of the CLAAS (CLoud property dAtAset using SEVIRI) data set and are generated by EUMETSAT's Satellite Application Facility on Climate Monitoring (CM SAF). In this art… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
(66 reference statements)
1
12
0
Order By: Relevance
“…Following Kniffka et al . (), a cloud is present in the model if CWP 0.05 mm. If this is true for a model grid box, then this grid box is assigned a value of 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following Kniffka et al . (), a cloud is present in the model if CWP 0.05 mm. If this is true for a model grid box, then this grid box is assigned a value of 1.…”
Section: Resultsmentioning
confidence: 99%
“…As CWP is derived from optical depth data using the relation from Stephens () depending on optical depth, we discard all observations showing CWP values less than 0.05 mm (Kniffka et al . ).…”
Section: Validation Data Setsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous research (Hobbs, 2002;McGill et al, 2003;Wilcox, 2010) has shown that the smoke is typically located in layers (at 2 to 4 km altitude) that are vertically separated from the Sc clouds below (at ∼ 1.5 km altitude) and, hence, direct microphysical interaction between the aerosols and the Sc is often inhibited by the strong temperature inversion above the cloud layer. However, more recent studies, e.g., Rajapakshe et al (2017), reported that smoke layers are closer to the cloud layer and significantly enhance the brightness of stratocumulus (Lu et al, 2018). Recently, several studies evaluated the dynamical and climatological impacts of the presence of smoke above Sc clouds from both modeling as well as satellite and/or field campaign measurements (Adebiyi et al, 2015;Adebiyi and Zuidema, 2016;Zuidema et al, 2016;Horowitz et al, 2017;Chang and Christopher, 2017;Lu et al, 2018;Kar et al, 2018).…”
Section: Effect Of Biomass Burning Smoke On Seviri and Modis Retrievalsmentioning
confidence: 99%
“…face temperatures (SSTs), within a shallow, well-mixed MBL capped by strong subsidence and a strong temperature inversion (e.g., Albrecht et al, 1995;Norris, 1998;Wood and Hartmann, 2006;Sandu et al, 2010). Several studies investigated the synoptic to inter-annual variability and the driving mechanisms of these clouds from both an observational and a modeling perspective (e.g., Klein and Hartmann, 1993;Klein et al, 1995;Bretherton and Wyant, 1997;Wood and Bretherton, 2006;Eastman et al, 2011;Wood, 2012;Painemal et al, 2012Painemal et al, , 2013aPainemal et al, , 2015Adebiyi et al, 2015;Adebiyi and Zuidema, 2016;Horowitz et al, 2017;Kar et al, 2018;Lu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%